Plasma Electrolytic Oxidation of Nanocomposite Coatings on Ti-6Al-7Nb alloy for Biomedical Applications - Qabas Khalid Naji; Jassim Mohammed Salman; Nawal Mohammed Dawood (مجلة بغداد للعلوم, 2024)
The current study aims to useTi-6Al-7Nb alloy instead of Ti-6Al-4V alloy in medical applications. Due to the poor hardness and wear that cause loose of the implant. The surface of Ti-6Al-7Nb alloy has been coated with titanium and zirconia/titanium oxide nanocomposite coating by Plasma electrolytic oxidation (PEO) process. The results of the tests showed the possibility of deposition of ceramics coatings on the surface of Ti-6Al-7Nb alloy by using different times. The ceramics layer of titanium oxide (TiO2) is formed during coating porous, homogenous distribution, and low corrosion rate and wettability. A composite nano ceramic layer was obtained from nano ZrO2 with TiO2 observed with increased thickness layer and concentration with time compared TiO2 layer improved percentage (90.5%) during the corrosion test, Hank's solution showed a strong ability to act as a barrier to prevent the localized corrosion attack from many aggressive ions.